VD_FINDINFO Pron / 2012 / 240 vom 25. Oktober 2012 - VD Tribunal cantonal (2012)
TRANSACTION JUDICIAIRE, FRAIS JUDICIAIRES, PROTECTION DE L'UNION CONJUGALE | 106 al. 2 CPC (CH), 241 al. 2 CPC (CH), 241 al. 3 CPC (CH), 65 al. 3 TFJC (2010), 67 al. 2 TFJC (2010)